Mobility as a Service for tourism: Challenges and opportunities for meeting the needs of tourists in urban environments - Iryna Vovk; Oleg Tson; Yuriy Vovk; Yaroslav Vovk; Nataliya Rozhko (Journal of Sustainable Development of Transport and Logistics)
Purpose: This study explores the challenges and opportunities of Mobility as a Service (MaaS) in meeting the needs of tourists in urban environments, aiming to provide insights into its potential for enhancing urban tourism mobility. Methodology: The research employs a mixed-methods approach, combining a systematic literature review, comparative case study analysis of four European MaaS schemes, and a conjoint choice experiment with 500 international tourists. Results: The study reveals that MaaS offers diverse mobility services catering to various tourist needs, with integrated transport modes and competitive pricing being the most valued attributes. Tourists demonstrate willingness to pay for enhanced MaaS features, with preferences varying across demographic segments. Key challenges identified include regulatory barriers, data sharing issues, and the need for stakeholder collaboration. Theoretical contribution: This research extends the understanding of MaaS in tourism contexts, addressing a significant gap in the literature. It provides a conceptual framework for analyzing MaaS in urban tourism and offers empirical evidence on tourist preferences and willingness to pay for MaaS attributes. Practical implications: The findings offer valuable insights for MaaS providers, urban planners, and policymakers in developing and implementing MaaS solutions tailored to tourist needs. The study highlights the importance of flexible package designs, stakeholder collaboration, and addressing regulatory challenges for successful MaaS implementation in urban tourism contexts.